PENGARUH KERJASAMA TIM DAN KEPERCAYAAN TERHADAP KOMITMEN GURU MTs DI JAKARTA SELATAN - Faizah Faizah (Universitas Negeri Jakarta, 2015)
The purpose of this research is to determine the effect of teamwork and trust on commitment of state madrasyah tsanawiyah teacher in south jakarta. The research methodology was survey which were selected by simple random sampling technique. Analysis and interpretation of the data indicate that (1) teamwork has a positive direct effect in commitment, (2) trust has a positive direct effect in commitment, (3) teamwork has a positive direct effect in trust.